Exome Sequencing Identified a Recessive RDH12 Mutation in a Family with Severe Early-Onset Retinitis Pigmentosa - Bo Gong; Bo Wei; Lulin Huang; Jilong Hao; Xiulan Li; Yin Yang; Yu Zhou; Fang Hao; Zhihua Cui; Dingding Zhang; Le Wang; Houbin Zhang (Journal of Ophthalmology)
Retinitis pigmentosa (RP) is the most important hereditary retinal disease caused by progressive degeneration of the photoreceptor cells. This study is to identify gene mutations responsible for autosomal recessive retinitis pigmentosa (arRP) in a Chinese family using next-generation sequencing technology. A Chinese family with 7 members including two individuals affected with severe early-onset RP was studied. All patients underwent a complete ophthalmic examination. Exome sequencing was performed on a single RP patient (the proband of this family) and direct Sanger sequencing on other family members and normal controls was followed to confirm the causal mutations. A homozygous mutation c.437T<A (p.V146D) in the retinol dehydrogenase 12 (RDH12) gene, which encodes an NADPH-dependent retinal reductase, was identified as being related to the phenotype of this arRP family. This homozygous mutation was detected in the two affected patients, but not present in other family members and 600 normal controls. Another three normal members in the family were found to carry this heterozygous missense mutation. Our results emphasize the importance of c.437T<A (p.V146D) substitution in RDH12 and provide further support for the causative role of this mutation in the pathogenesis and clinical diagnosis of RP.